Analisis Strategi Pemasaran dalam Meningkatkan Penjualan Motor - Roswita Sari; Ismaniar Rey Pati; Inelda Bulu; Astuti Louru Warata; Afelino Donbosco Bili (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
This study aims to analyze effective marketing strategies in increasing motorcycle sales amidst increasingly tight automotive industry competition. In this analysis, the main focus is given to identifying factors that influence consumer purchasing decisions, including price, product quality, promotion, and distribution. Data were collected through interviews with marketing managers at several leading motorcycle dealers and surveys of consumers who had just purchased a motorcycle. The results of the study indicate that a combination of marketing strategies that include attractive promotions, understanding local market needs, and improving the overall consumer experience play a significant role in increasing motorcycle sales volume. This study concludes that implementing the right marketing strategies, such as the use of social media, seasonal discounts, and improving after-sales service, can have a positive impact on motorcycle sales growth. It is recommended for companies to continue to innovate and adjust marketing strategies to evolving consumer trends and preferences.